Prediction of Land Use/Land Cover Change in the New Telaga City Plan Area, Gorontalo Province - Gani, Regita Chahyani Abdul; Munibah, Khursatul; Pravitasari, Andrea Emma (Universitas Negeri Gorontalo, 2026)
The development of the Telaga City planning area as a new city in the peri-urban area controls urban expansion while promoting equitable development and economic growth. However, high pressure from population growth, economic growth, and the need for developed land in peri-urban areas risks triggering land use incompatibility and a decline in environmental quality. In anticipation of these threats, this study aims to predict changes in land use/land cover (LU/LC) in the Telaga City planning area as a basis for future spatial planning. This research is experimental in nature, testing the influence of regional dynamics on changes in LU/LC. The novelty of this research lies in the use of high-resolution SPOT 6/7 image interpretation LU/LC maps, which enable more detailed and accurate identification of changes in LU/LC. The methods used include (1) Euclidean distance and data normalization to obtain data ready for use in the prediction process; and (2) Pearson correlation, Artificial Neural Networks (ANN), Cellular Automata (CA), and Kappa Accuracy for the prediction process. The analysis results show that the ANN model is able to capture the nonlinear relationship between driving factors and land transitions well, as indicated by a kappa validation accuracy value of 91.69%. The prediction results for the 2023–2033 period show that the dominance of vegetated areas will continue, but residential/mixed-use land will experience consistent growth, especially in the southern part, indicating strong urban development pressure. Therefore, the results of this study emphasize the need for LU/LC planning and control to minimize land use incompatibility.